Pengaruh Strategi Digital Marketing Oleh Pelaku UMKM Terhadap Keputusan Pembelian Masyarakat Muslim di Provinsi Jambi - Dean Amry, Ary; Aeni, Ika Nur; Salsabilah, Avia; Kurniawan, Ilham Bagus (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2023)
Digital marketing is a medium and method that is currently widely used by MSME players in encouraging their business activities, especially in promoting a product through internet media with a wider range of consumers. With this digital marketing, it turns out that it results in the decision of the Muslim community towards digital marketing, where there are factors that influence the purchasing decisions of Muslim communities in online media such as service, promotion and price. The purpose of this research is to find out how the influence of digital marketing strategies on the purchasing decisions of Muslim communities on online media in Jambi Province. This study uses quantitative methods with a population of Muslim communities in Jambi Province. Data collection by distributing questionnaires to 400 samples of residents of Jambi Province which are divided into 11 districts. The aspects examined in this study, namely the digital marketing strategy, are service, promotion, price and interest factors. The results of this study indicate the results of the digital marketing variable validity test on all statement items rhitung (0.529)> rtabel (0.098) so that the 6 statement items in the digital marketing variable are declared valid. In the validity test of the purchasing decision variable, it is known that all question items rcount (0.394) > rtable (0.098) with a significance value (p value) <0.05 so that the 2 statement items in the purchasing decision variable are declared valid. Based on the results of the simple regression test, it shows that the digital marketing variable has a tcount value (1.187)> ttable (0.098) with a probability value of 0.000, which is smaller than 0.05, so Ha is accepted. This means that digital marketing has a significant effect on the purchasing decisions of the Muslim community of Jambi Province on online media. The output results also obtained a coefficient of determination (R Square) of 0.735, which means that 73.5% digital marketing is able to attract the buying interest of the Jambi Province Muslim community in online media. While the remaining 26.5% is influenced by other factors not examined in this study